2020
DOI: 10.1186/s40798-020-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effects of Androgen Deprivation Therapy in Prostate Cancer and the Benefits and Potential Anti-oncogenic Mechanisms of Progressive Resistance Training

Abstract: Prostate cancer has the second highest incidence of all cancers amongst men worldwide. Androgen deprivation therapy (ADT) remains a common form of treatment. However, in reducing serum testosterone to castrate levels and rendering men hypogonadal, ADT contributes to a myriad of adverse effects which can affect prostate cancer prognosis. Physical activity is currently recommended as synergistic medicine in prostate cancer patients to alleviate the adverse effects of treatment. Progressive resistance training (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 151 publications
0
13
0
1
Order By: Relevance
“…Most prostate cancer patients do not have obvious early symptoms, often in the physical examination accidentally found [ 15 ]. Worse, when prostate cancer progresses, surgical resection is no longer beneficial, due to its high recurrence; however, chemoradiotherapy has no significant effect on improving the prognosis of patients, and chemoradiotherapy has strong side effects [ 16 ]. In conclusion, targeted therapy is the most effective treatment for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most prostate cancer patients do not have obvious early symptoms, often in the physical examination accidentally found [ 15 ]. Worse, when prostate cancer progresses, surgical resection is no longer beneficial, due to its high recurrence; however, chemoradiotherapy has no significant effect on improving the prognosis of patients, and chemoradiotherapy has strong side effects [ 16 ]. In conclusion, targeted therapy is the most effective treatment for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, such long-term use of hormone activity manipulators seems to be having undesirable effects in a number of health areas, including but not limited to libido [ 185 ]: around 15,000 post-finasteride adverse effects at a clinically relevant level have been reported to an online forum (pfsfoundation.org), perhaps implying a more widespread relevance of androgen signaling in man than just in the prostate, although the recent re-evaluation of the PCPT trial largely refuted a finasteride-based mechanism for these effects [ 182 ]. As the number of patients on long-term maintenance of prostate cancer remission with ADT increases, more evidence accumulates about potential physical effects of androgen suppression, including decreases in bone mineral density, metabolic changes such as weight gain, decreased muscle mass, and increased insulin resistance, decreased libido and sexual dysfunction, hot flashes, gynecomastia, reduced testicle size, anemia, and fatigue [ 186 ].…”
Section: Does Better Androgen Blockade Change the Natural Historymentioning
confidence: 99%
“…Rates of implantation after prostate cancer treatment remain low despite high levels of satisfaction. 52 53,54 Simple measures can improve mental health and confidence, giving men a more positive outlook on rehabilitation. One study of men undergoing ADT, observed significantly higher levels of sexual interest in those who underwent a 12-week exercise programme.…”
Section: Erectile Aidsmentioning
confidence: 99%